Biotechnology in genetics and reproduction - Smidt, D.; Niemann, H. (Livestock production science, 1999)
Biotechnology is a key technology in the generation of an adequate food supply for the ever growing human population. Genetics and reproduction as fundamental functional prerequisites for successful livestock production have been important subjects of biotechnological research in animal science for many decades. Biotechnological procedures developed so far are to be applied for increasing breeding efficiency in farm animals, for the preservation of animal genetic resources, for the improvement of product quality or for new production strategies and novel animal products. Many of these opportunities are already routine in animal husbandry, others will be employed according to needs, suitability and their public perception. The latter has to be addressed by observing the ethical principles for the application of biotechnology in animals in selected areas of livestock production in which immediate benefits are to be obtained. This paper deals with some of the future perspectives and visions for animal biotechnology in research and field application. It focusses on cryopreservation of germ cells and embryos, ovum pickup from ovaries in situ and IVMFC, gender preselection, cloning, genome analysis and gene mapping, and gene transfer.